Língua portuguesa para surdos do ensino médio: uma proposta de sequência didática bilíngue com o gênero textual "charge" - Rosa, Maiara Scherer Machado (2021)
This master's thesis aims to present a proposal for a bilingual didactic sequence for deaf high school learners involving the teaching of Portuguese as L2. To meet the objective, we opted for the theory of textual genres, presented by the scholar and linguist Marcuschi, articulated to bilingual studies for the deaf. With regard to the creation of the proposal for a didactic sequence, it starts with theorists Dolz, Noverraz, Schneuwly (2004) and the expansion of these concepts to sign languages, defended by Cezar (2018) and his later advisees (ALMEIDA, 2018; INÁCIO , 2018; THAYSE 2019; SOUZA, 2020). The educational theme and data motivating the difficulties presented by deaf learners come from the collection of data from the extension project “Teaching-Learning of the Portuguese Language in Written Modality (L2) for the Deaf”, a project filed with the UNIOESTE/ Foz, in 2016. The results of the analyzes showed the need to reflect on how to propose a Portuguese language teaching in the written modality that respects the linguistic differences of the deaf people. With the purpose of finding answers to this problematization, we composed a bilingual didactic sequence (SDB), since, in this proposal, the visual elements that converge with the linguistic aspects of Libras stand out. From studies and empirical knowledge on the subject, the following questions emerged that guided this research: What are the specificities of teaching Portuguese to deaf students in a bilingual perspective? How to create a bilingual didactic sequence to teach the cartoon genre, respecting the peculiarities of the deaf student? With the purpose of finding answers to this problematization, the general objective is centered on the SDB and all possible teaching proposals with textual genres. This material will be a resource for bilingual teachers. It is, therefore, a qualitative and bibliographic research. The results demonstrate that all specificities, such as: bilingual teaching, bilingual teacher/student, visual aspects, linguistic comfort, relevant/sensitive teaching, looking at the student's knowledge of the world and conducting work based on it, leads students and teachers to work with two languages of different modalities in a lighter way and with more satisfactory results.